EFFECT OF NEWS COMMERCIALIZATION ON AUDIENCE PERCEPTION OF REALITY IN NIGERIA: A REVIEW OF PROPAGANDA MODEL - Oloyede, Oyinloye; Okoji, Morenikeji Chukwufumnaya; Agwolo, Nyeumazu Goodluck; Azeez, Memunat Abiola; Okoji, Chukwudinma Taiwo (African Journal of Social and Behavioural Sciences, 2024)
This study investigates the influence of the Propaganda Model on news commercialization and its impact on the audience’s perception of reality. Two specific objectives were formulated, with the Social Responsibility Theory serving as the theoretical framework guiding the study. Secondary data collection methods were employed, and a Systematic Review approach was utilized to analyse the literature on news, news commercialization, and the Propaganda Model proposed by Herman and Chomsky. The findings of the study revealed several key determinants and elements of news, including prominence, proximity, impact, immediacy, conflict, oddity, consequence, and human interest. Additionally, the study identified major features and characteristics of news, such as objectivity, truthfulness, balance, fairness, accuracy, conciseness, clarity, brevity, and recency. Furthermore, the study outlined five filters driving news commercialization according to the Propaganda Model: size, ownership and profitability, advertisers’ influence, sources. In order to mitigate the effects of commercialization, the study recommends a reinvention of media content to enable media outlets to fulfil their potential as agents of national development rather than tools for ideological reinforcement by capitalist interests. Moreover, it suggests that journalists should be adequately compensated and provided with regular training and retraining opportunities to ensure they adhere to journalistic ethics and fulfil their societal roles effectively. Media owners are urged not to prioritize profit over public affairs issues, but to explore alternative revenue generation methods such as investment and fundraising. Additionally, relevant regulatory agencies are encouraged to enhance their monitoring responsibilities to ensure that public interest is not compromised for financial gains within the media landscape.